2018
DOI: 10.1111/jonm.12670
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude between patients and their families and health professionals: A scoping review

Abstract: Gratitude from patients and their families may contribute to motivation and retention among health professionals. Gratitude can be nurtured and is associated with a healthy work environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 71 publications
(147 reference statements)
3
31
1
3
Order By: Relevance
“…A scoping review of 32 articles on gratitude identified the impact this feedback had on the recipients; however, the effect on the person expressing gratitude was lacking. 6 Gratitude has been described as a complex, contextual emotion that is not necessarily deserved or earned. 7 More recently, it is described as an appreciation of experiences rather than receiving a gift or service, the appreciation of what is valuable and meaningful, and represents a general state of thankfulness.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…A scoping review of 32 articles on gratitude identified the impact this feedback had on the recipients; however, the effect on the person expressing gratitude was lacking. 6 Gratitude has been described as a complex, contextual emotion that is not necessarily deserved or earned. 7 More recently, it is described as an appreciation of experiences rather than receiving a gift or service, the appreciation of what is valuable and meaningful, and represents a general state of thankfulness.…”
Section: Key Pointsmentioning
confidence: 99%
“…11 Although various studies have identified nursing behaviors associated with meaningful recognition and positive patient experiences, the knowledge regarding what it means to patients/families to express gratitude is lacking. 6…”
Section: Key Pointsmentioning
confidence: 99%
“…Si bien el concepto se encuentra presente en todo el mundo y en todas las culturas, de una u otra forma, no se encuentra libre de controversia, existiendo diversos autores que lo han definido de diferentes maneras que pueden llegar a ser bastante disímiles, sin necesariamente ser dichas conceptualizaciones excluyentes entre sí [6][7][8] . Ha sido descrita como un estado emocional, como un rasgo, como una respuesta de afrontamiento, como una virtud moral, como un hábito, como una actitud y como una orientación de vida, sin embargo, las dos aproximaciones más frecuentemente utilizadas en investigación empírica son como rasgo o disposición y como estado afectivo 9,10 . Como rasgo o disposición usualmente alude a la tendencia individual y generalizada a notar y experimentar aprecio por lo bueno en la vida, presentando aquellos con mayor gratitud disposicional una mayor tendencia a sentir gratitud con mayor frecuencia, intensidad y ante una mayor variedad de personas o estímulos 8 .…”
Section: El Concepto De Gratitudunclassified
“…Como rasgo o disposición usualmente alude a la tendencia individual y generalizada a notar y experimentar aprecio por lo bueno en la vida, presentando aquellos con mayor gratitud disposicional una mayor tendencia a sentir gratitud con mayor frecuencia, intensidad y ante una mayor variedad de personas o estímulos 8 . Por su parte, la gratitud como estado emocional o afectivo alude a una sensación que surge cuando uno reconoce que ha obtenido un resultado valorado personalmente como positivo de una fuente externa 7,10 . Generalmente implica que la persona percibe que recibe un beneficio valioso, sobre todo si no fue buscado, merecido, ganado o secundario a intenciones ocultas de un otro, esto ya sea en relación a un acto de generosidad por un benefactor concreto, o por otras fuentes impersonales como podrían ser un evento, la naturaleza o Dios 8,11,12 .…”
Section: El Concepto De Gratitudunclassified
See 1 more Smart Citation